Not Lost at Sea: The Ajax Club of Halifax - Cross, Wes (The Northern Mariner / Le marin du nord, 2025)
Halifax was known as the least favourite wartime Atlantic port for sailors and roundly received criticism for the treatment of sailors ashore. The fate of the Ajax Club became a much-cited example of that belief. In May 1945 that displeasure would infamously come to a head in the V-E Day riots. The Ajax Club story and the naval badges received from ships’ crews and naval authorities are a reminder of the uncertainty of public memory. The efforts and legacy of a civilian woman was a local story that played an unexpectedly larger role in wartime Canada and in subsequent years.